Crack Propagation and Fragmentation Characteristics of Single-Flawed Sandstone Samples under Different Loading Conditions - Lei, Wen; Wenjie, Feng; Mingye, Li; Junhong, Yu (Shock and Vibration, 2023)
Red sandstone specimens with preexisting single flaw were taken as the research object in the static and dynamic loading tests. A hydraulic press was used for the uniaxial compression experiment, and SHPB was used for the impact test. The corresponding static and dynamic stress-strain curves were obtained. The crack propagation of rock samples under different loading conditions was obtained using the camera system. The crack propagation, compressive strength, and energy characteristics of samples under quasi-static and dynamic impact loading were analyzed. The findings show that the crack initiation, development, and final fracture mode of the samples are closely related to the inclination angle of preexisting flaw and strain rate. Compared with samples under static loading, tensile and shear mixed cracks, layer separation cracks, and more far-field cracks appeared in the samples under dynamic loading. With the increase of the peak of incident wave during the SHPB test, the samples with preexisting flaw change from tensile crack to X-shaped shear failure in the range of medium strain rate. Under different loading conditions, the compressive strength of samples with 45° crack is the lowest. The energy dissipation density and energy dissipating rate of the single-flawed specimens feature a rising trend with the increasing peak of incident wave, and the influence of the inclination angle of preexisting flaw on the energy dissipation is significant for a given peak of incident wave. The strength, energy dissipation, and fractal dimension of the specimens are positively correlated with each other under different strength impact loading. As the peak of incident wave increases, the inclination angle of preexisting flaw has more significant influence on the interrelation of these three parameters.